UI/UX Prototyping for Mobile Legends Quick Application Through The Design Thinking Method (Case Study: Mobile Legends E-Sport) - Fathona Hasibuan, M. Ikmal; Setiawan, Dadang; Sulistiyo Kusumo, Dana (PT Mattawang Mediatama Solution, 2023)
Designing user interface prototyping and user experience aims to manage access to information easily for the e-sport game of Mobile Legends users. The application prototype contains match schedules, players, e-sport teams, match highlights, match analysis, and others. The reason is that when the users want to get such information, they must find it from various media without any data being immediately available. It is the appropriate way to develop a Mobile Legends Quick prototype application. The prototyping process in creating mobile applications uses the stages in design thinking method stages of Empathize, Define, Ideate, Prototype, and Test. The scope of these goals preferably has a user-centered approach and user satisfaction to solve relevant problems and create new innovations. The results of the tests carried out on making prototype application have been tested using The System Usability Scale (SUS) and obtained a result of 85,35%, with the acceptable category and excellent grade from the SUS score acquisition.